Numerical study of the parameters in an arbitrary order SIR model built with Mittag-Leffler distribution - Monteiro, Noemi Zeraick; Mazorche, Sandro Rodrigues (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
We previously discussed the construction of an arbitrary order SIR model with physical meaning. We believe that arbitrary order derivatives can be obtained through Mittag-Leffler based laws in the infectivity and removal functions. Here we are interested in obtaining information about the influence of the parameters in the studied model, with the aim of promoting its use and strengthening the biological interpretation.
Keywords: Arbitrary order derivatives; SIR model; MittagLeffler; Parameter analysis.